Financial Leverage Dynamics: The Roles of Liquidity and Profitability in Shaping Firms’ Financial Health - Rida Nazeer; Faiza Saleem; Muhammad Yusuf Amin (Audit and Accounting Review, 2025)
The current study investigates the relationship between financial leverage (FL), profitability, and liquidity among non-financial firms listed on the Karachi Stock Exchange (KSE) in Pakistan. Despite extensive research on capital structure and profitability, limited studies exist on the debt structure and liquidity exist, particularly in the developing economies where concentrated ownership patterns are prevalent. The study used a panel dataset of 305 firm-year observations from 50 non-financial firms for the time period 2016-2022. The study applied a Random Effects Model (REM) or Generalized Method of Moments (GMM) for empirical analysis and found that profitability is positively related to financial leverage, as profitable firms use more debt to maximize tax benefits, while liquidity is negatively related, suggesting firms use lower debt to mitigate financial distress costs. The study provides practical implications for companies, investors, corporate managers, and policymakers to select the optimal capital structure. This emphasizes the importance to understand liquidity and the positive relationship between PROF and FL. It suggests that wise debt use can maximize tax benefits and balance financial risks, particularly in developing markets. Policymakers should create tax policies to promote investments while mitigating risks. The study also highlights the need for further research by incorporating more control variables and extending the analysis across different markets and time periods.